The influence of non-selective arginase inhibitors on some reparative regeneration indexes of experimentally resected liver - Kolesnik, Inga. M; Zhernakova, Nina I.; Osipova, Olga A.; Batischeva, Galina A.; Galenko-Yaroshevsky, Pavel A.; Dolzhikov, Alexander A. (AVFT – Archivos Venezolanos de Farmacología y Terapéutica, 2021)
The impact of L-norvaline, a non-selective arginase inhibitor, on the state of the resected liver of Wistar strain white male rat, was evaluated. The resection of the liver was made on the second day of the experiment to the extent of 70%. L-norvaline ("WIRUD JmgH", Hamburg) was intragastrically administered, at a daily dose of 18mg/kg for the first seven days of the experiment, every 48 hours. The effect of the drug on the state of the resected liver was assessed according to the mortality rate, time of the volume recovery, the structure and functions of the organ. The mortality rate was being assessed in the experimental animal groups for the first ten days after the surgery. The animals were withdrawal from the experiment on the second, seventh, fourteenth, twenty-first, and twenty-eight days after the surgery. The cytolysis degree was assessed according to the AlAT, AsAT, and LDH indexes in the blood of the experimental animals, by an ultraviolet kinetic method. The synthesis function of the liver was evaluated according to the coagulogram indexes (APPT, INR, fibrinogen). The level of microcirculation in the liver was determined by laser doppler fluorometry. The morphological study was performed on the material of the standard liver sites taken after the animal had been withdrawal from the experiment. It was shown, that the non-selective arginase inhibitor, L-norvaline, stimulates liver regeneration after resection, which is manifested by decreased lethality, a significant decrease in the post-resection liver failure in comparison with the control group; significant earlier restoration of the volume, structure, and functions of the resected organ compared with the control group.